Optimizing Zakat Collection in the Digital Era: Muzakki's perception - Muhammad Syafii Antonio; Sugiyarti Fatma Laela; Dhimas Mukhlas Al Ghifari (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
This study aims to examine determinants of zakat payers’ (muzakki) interest to pay zakat through Zakat Management Organization (ZMO). The respondents were randomly selected from muzakki who paid their zakat on profession/income through ZMOs in Indonesia resulting in 100 respondents. Using Structural Equation Modelling (SEM) method, this study found that transparency of zakat management, ZMO promotions using public figures, and supporting regulation which imposes zakat as a tax deductible expense have significant impact on muzakki's interest to pay zakat through ZMO. Meanwhile improvement of digital services and socialization of zakat through social media do not have significant effect on muzakki's interest. However, using sub-sample who are active users of social media, this study discovered a negative effect of social media usage on muzakki’s interest. This finding reinforces the suitability of Theory of Planned Behavior (TPB) in the context of muzakki's behavior to pay zakat which is influenced by the quality of ZMO services.